If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -18 = m + -4 + 14 Combine like terms: 6 + -18 = -12 -12 = m + -4 + 14 Reorder the terms: -12 = -4 + 14 + m Combine like terms: -4 + 14 = 10 -12 = 10 + m Solving -12 = 10 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -12 + -1m = 10 + m + -1m Combine like terms: m + -1m = 0 -12 + -1m = 10 + 0 -12 + -1m = 10 Add '12' to each side of the equation. -12 + 12 + -1m = 10 + 12 Combine like terms: -12 + 12 = 0 0 + -1m = 10 + 12 -1m = 10 + 12 Combine like terms: 10 + 12 = 22 -1m = 22 Divide each side by '-1'. m = -22 Simplifying m = -22
| (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 | | -5x+5(8x-6)=180 | | A=7/4 | | a+2=6a-6 | | 3t^3-30t^2-21t=0 | | 22=5a |